MICROENCAPSULATION TECHNIQUE FOR SELECTED PROBIOTICS AND PREBIOTICS - D, Ravi; G, Usha; R, Parthasarathy (Malaysian Journal of Science, 2013)
Nowadays probiotics and prebiotics require full attention to stay viable in the food industry and the medical field. Microencapsulation is performed generally to give a protective covering for probiotics and prebiotics thereby saving from the spoilt environment. The Microencapsulation study is mainly performed in order to approve the viability of probiotics for better mode of action in food, health care and other applications. Prebiotics and sodium alginate was used as a coating material in order to microencapsulate probiotics (Lactobacillus rhamnosus and Lactobacillus plantarum). This research depicts the survival rate of encapsulated probiotics (L.plantarum and L.rhamnosus) with/without prebiotics over a period of one month. (Key words: Microencapsulation, Probiotics, Prebiotics, Lactobacillus plantarum, Lactobacillus rhamnosus)